[Evaluation of Bispectral Index time delay in response to anesthesia induction: an observational study] - Ferreira, Ana Isabel Leitão (2019)
Background and objectives: According to the manufacturer, the Bispectral Index (BIS) has a processing time delay of 5-10s. Studies addressing this have suggested longer delays. We evaluated the time delay in the Bispectral Index response. Methods: Based on clinical data from 45 patients, using the difference between the predicted and the real BIS, calculated during a fixed 3minutes period after the moment the Bispectral Index dropped below 80 during the induction of general anesthesia with propofol and remifentanil. Results: The difference between the predicted and the real BIS was in average 30.09±18.73s. Conclusion: Our results may be another indication that the delay in BIS processing may be much longer than stated by the manufacture, a fact with clinical implications.